Three-dimensional dislocation dynamics modelling of particle-reinforced ferrous alloys for nuclear applications - Thompson, D (2015)
An existing point defect bulk diffusion model of dislocation climb is developed to incorporate both vacancies and interstitials, and supersaturations of these defects. Calculations are carried out for body-centred cubic (bcc) iron using this model, which show that the interstitial nature of experimentally observed irradiation-induced damage loops can be explained by the preferential osmotic absorption of supersaturated interstitials over vacancies by damage loops. The model is implemented into a 3D dislocation dynamics code, together with a dual glide and climb time step method, and spherical obstacles which are impenetrable to dislocations, all of which required original code development. Simulations of dislocation-inclusion unpinning via climb in particle-reinforced bcc iron are conducted, and the creep strain rate is estimated from the unpinning time data. The thermal creep strain rates are seen to be strongly temperature-dependent, as expected. Varying the applied load and dispersion properties is seen to have a relatively small effect, and remarkably the creep rates exhibit no dependence on the particle size and number density for a given volume fraction of obstacles. The thermal creep strain rates predicted are consistent with experimental observation. The irradiation creep strain rates are seen to vary much less strongly with temperature, also as expected. These results suggest that in particle-reinforced alloys under advanced nuclear reactor operating conditions, it is possible the irradiation creep rate will be orders of magnitude larger than the thermal creep rate at this temperature, depending on the value of the steady-state point defect supersaturations available to drive dislocation climb. In this case, the use of such alloys for advanced nuclear applications will be somewhat limited.